Antifungal activity of six plant essential oils from Serbia against Trichoderma aggressivum f. europaeum (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Six essential oils (EOs) extracted from plants originating in Serbia were assayed forinhibitory and fungicidal activity against a major fungal pathogen of button mushroomcausing green mould disease, Trichoderma agressivum f. europaeum. The strongest activity was demonstrated by the oils of basil (Ocimum basilicum L.) and peppermint (Mentha piperita L.). Medium antifungal activity of St. John's wort (Hypericum perforatum L.) and walnut [Juglans regia (F)] oils was also recorded. Oils extracted from yarrow (Achillea millepholium L.) and juniper (Juniperus communis L.) exhibited the lowest activity. Peppermint oil showed fungicidal effect on the pathogen, having a minimum fungicidal concentration of 0.64 μl ml-1. The main components of peppermint essential oil were menthone (37.02%), menthol (29.57%) and isomenthone (9.06%).
Keywords: Esential oils; Trichoderma; Edible muhsrooms